2021
DOI: 10.3390/ma14082078
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Wheat Straw Ash as Partial Sand Replacement for Production of Eco-Friendly Concrete

Abstract: The depletion of natural sand resources occurs due to excessive consumption of aggregate for concrete production. Continuous extraction of sand from riverbeds permanently depletes fine aggregate resources. At the same time, a major ecological challenge is the disposal of agricultural waste ash from biomass burning. In this study, an environmental friendly solution is proposed to investigate the incorporation of wheat straw ash (WSA) by replacing 0, 5, 10, 15, and 20% of sand in concrete. Characterization resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 64 publications
1
6
0
Order By: Relevance
“…It can be observed that the compressive strength was higher for lower w/c ratios (w/c = 0.4). This trend suggests that the density is directly proportional for conventional concretes, and similar conclusions can be found for other organic materials used as replacements for fine aggregates [55]. However, this relationship did not hold for concretes with higher percentages of hazelnut shell, which is lighter and more porous than regular aggregates.…”
Section: Influence On Compressive Strengthsupporting
confidence: 61%
“…It can be observed that the compressive strength was higher for lower w/c ratios (w/c = 0.4). This trend suggests that the density is directly proportional for conventional concretes, and similar conclusions can be found for other organic materials used as replacements for fine aggregates [55]. However, this relationship did not hold for concretes with higher percentages of hazelnut shell, which is lighter and more porous than regular aggregates.…”
Section: Influence On Compressive Strengthsupporting
confidence: 61%
“…The utilization of biomass aggregate for concrete preparation can effectively improve the energy consumption of buildings. Some researchers have found [6][7][8][9][10][11][12][13] that when concrete is prepared using biomass aggregates such as pine needles, canola straw, coconut husk, corn cob, and corn stover, density and thermal conductivity decrease with the increase of biomass aggregates. In addition, some of the durability properties and plasticity were improved.…”
Section: Introductionmentioning
confidence: 99%
“…The concrete industry puts a strain on some finite natural resources, such as sand [4] and water [5]. By substituting sand with organic waste materials, various active and passive advantages can be achieved, such as the mitigation of environmental challenges related to sand consumption, the reduction of costs and environmental issues linked to the amount of organic waste disposal and management, and the possibility to store carbon in concrete through organic waste.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the compressive strength decreases with increasing the share of corncob ash in the mix. Replacing 10% of aggregates with wheat straw ash has been found to increase the compressive strength of concrete [4]. The use of rice husk ash has been previously investigated as a partial cement substitute in concrete [15].…”
Section: Introductionmentioning
confidence: 99%